2021
DOI: 10.1186/s12939-021-01432-3
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding at the workplace: a systematic review of interventions to improve workplace environments to facilitate breastfeeding among working women

Abstract: Background Breastfeeding can be affected by maternal employment. This is important considering that in 2019, 47.1% of women globally participated in the labor force. The aim of this study was to review workplace interventions to promote, protect and support breastfeeding practices among working mothers globally. Methods A systematic review was conducted following the guidance of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 48 publications
4
71
0
1
Order By: Relevance
“…It is linked to a change in the working culture, including demystifying BF as feminine, and any machoistic view that implies that is incompatible with work and productivity. All of it is consistent with the findings of a recent systematic literature review [ 9 ]. Moreover, the Becoming Breastfeeding-Friendly (BBF) Committee in Mexico recommended that Mexico should work towards having better conditions for BF working mothers including a BF-friendly working environment [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is linked to a change in the working culture, including demystifying BF as feminine, and any machoistic view that implies that is incompatible with work and productivity. All of it is consistent with the findings of a recent systematic literature review [ 9 ]. Moreover, the Becoming Breastfeeding-Friendly (BBF) Committee in Mexico recommended that Mexico should work towards having better conditions for BF working mothers including a BF-friendly working environment [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Both Chang´s systematic review as well as our study show the role of supervisors and colleagues as an important barrier or facilitator for working mothers to continue BF once they return to work. Finally, consistent with a recent systematic review aiming to describe workplace interventions to promote, protect and support BF practices among working mothers globally (which included quantitative and qualitative studies) [ 9 ], the present study identified the poor knowledge on legislation to protect maternal and child health, including BF, among working women, employees, and co-workers. Taken together, all studies highlight the importance of developing written policies at different levels (national, local and within each worksite) as well as educating co-workers, directors, human resources personnel and mothers about the importance of BF and the local maternity protection legislation to promote a BF-friendly environment.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…On the contrary, part-time work has been found to have a positive impact on breastfeeding duration [86,87]. Flexibility in working schedules may be associated with breastfeeding [88]. Despite no studies, the acceptance of teleworking following the COVID-19 pandemic could also help women to breastfeed [89].…”
Section: Other Factors Influencing Breastfeeding After Returning To Workmentioning
confidence: 99%
“…Excessive workload, caesarean section delivery, discouragement and criticism inadequate creche facilities at the workplace, inadequate caregivers at home, inadequate knowledge about expressed milk are barriers to EBF for employed mothers [ 44 , 45 ]. Evidence suggested a baby-friendly workplace for employed mothers was effective for improving EBF practices [ 46 , 47 ]. Also, better knowledge, education, counselling, home support, six-months maternity leave, and flexibility at work are the enablers of exclusive breastfeeding for employed mothers in LMICs [ 44 , 48 ].…”
Section: Discussionmentioning
confidence: 99%